Metformin suppresses epithelial sodium channel hyperactivation and its associated phenotypes in a mouse model of obstructive lung diseases - Ryunosuke Nakashima; Hirofumi Nohara; Noriki Takahashi; Aoi Nasu; Megumi Hayashi; Tomoki Kishimoto; Shunsuke Kamei; Haruka Fujikawa; Kasumi Maruta; Taisei Kawakami; Yuka Eto; Keiko Ueno-Shuto; et al. (Elsevier, 2022)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death in the world, and has no radical treatment. Inhibition of amiloride-sensitive epithelial sodium ion channel (ENaC) has now been considered as a potential therapeutic target against COPD. One possible modulator of ENaC is AMP-activated protein kinase (AMPK), a key molecule that controls a wide variety of cellular signals; however, little is known about whether metformin, a clinically available AMPK activator, has a protective role against ENaC-associated chronic pulmonary phenotypes, such as emphysema and pulmonary dysfunction. We first used ENaC-overexpressing human bronchial epithelial cells (β/γENaC-16HBE14o-) and identified that Metformin significantly reduced ENaC activity. Consistently, in vivo treatment of ENaC-overexpressing COPD mouse model (C57BL/6-βENaC-Tg mice) showed improvement of emphysema and pulmonary dysfunction, without any detrimental effect on non-pulmonary parameters (blood glucose level etc.). Bronchoalveolar lavage fluid (BALF) and lung tissue analyses revealed significant suppression in the infiltration of neutrophils as well as the expression of inflammatory markers (KC), neutrophil gelatinase (MMP9) and macrophage elastase (MMP12) in metformin-treated C57BL/6-βENaC-Tg mice. Overall, the present study demonstrates that metformin directly inhibits ENaC activity in vitro and provides the first evidence of therapeutical benefit of Metformin for COPD with higher ENaC activity.